Analisis Kesehatan Masyarakat Berdasarkan Ruang Lingkup Kependudukan dan Ketenagakerjaan di Kelurahan Pegirian Kecamatan Semampir Kota Surabaya - Nuria Nuria; Yuly Sulistyorini (Universitas Airlangga, 2018)
WHO (1947) defined health as a perfect condition both physically, mentally and socially and not only free from disease. The socio-economic aspect states the meaning of health if the community is able to advance its life by learning, working, or interacting with its surroundings. Public health in terms of socio-economic aspects can be seen from the conditions of population and employment. Through these two things, it can be seen the level of community welfare that can support the achievement of public health. Therefore, it is necessary to analyze population and employment conditions in Pegirian Village. This study will make it easier to carry out health-oriented development planning in order to achieve public health. This research is descriptive research with cross sectional approach. Research was conducted at RT 06 RW 02 Pegirian Village. Research was done at January 2018. This research was using secondary data from field work practices report of student FKM UNAIR 2018. Age data, gender, education, job, and tribe were used in this research. The results showed that the male population was 52.63%. The population aged 15-64 years was 70.18%. As many as 93.86% of the population was Madura Tribe. The percentage of the population that works and has the last primary education level or less was 68.29%. The population generally worked at 73.68%. Work force was 39.47%. LFPR was 53.57% and open unemployment rate was 8.89%. Public health conditions from the scope of population and employment in RT 06 RW 02 Pegirian Village Semampir Subdistrict are not good enough. Although, the population of productive age is high, the LFPR is still low. In addition, the level of education is still low so the quality of labor is also low.